2021
DOI: 10.1002/chem.202005004
|View full text |Cite
|
Sign up to set email alerts
|

Multiply Charged Helium Droplet Anions

Abstract: The detectiono fm ultiply charged helium droplet anions is reported for the first time. By ionizing droplets of superfluid helium with low energy electrons (up to 25 eV), it was possible to produce droplets containing up to five negative charges, which remaini ntact on the timescale of the experiment.T he appearance sizes for differentc harge states are determined and are found to be orders of magnitude largert han for the equivalentc ationic droplets, starting at 4 millionH ea toms for dianions. Droplets with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 30 publications
2
21
0
Order By: Relevance
“…In contrast to the single-collision conditions typically used for electron scattering experiments with molecular or atomic targets, the huge geometric cross section of the investigated helium droplets and the high electron currents chosen in the present study ensured multi-collision conditions, with up to several hundred electron hits per droplet. As was already reported previously [33,34], the mass loss due to neutral He evaporation or asymmetric Coulomb explosion was negligible, and so the interaction of electrons with large He droplets essentially only changed their charge states. Individual relative cross section curves for charging positively charged He droplets clearly showed that with increasing electron energy product, the droplets were preferentially ending up in higher charge states.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…In contrast to the single-collision conditions typically used for electron scattering experiments with molecular or atomic targets, the huge geometric cross section of the investigated helium droplets and the high electron currents chosen in the present study ensured multi-collision conditions, with up to several hundred electron hits per droplet. As was already reported previously [33,34], the mass loss due to neutral He evaporation or asymmetric Coulomb explosion was negligible, and so the interaction of electrons with large He droplets essentially only changed their charge states. Individual relative cross section curves for charging positively charged He droplets clearly showed that with increasing electron energy product, the droplets were preferentially ending up in higher charge states.…”
Section: Discussionsupporting
confidence: 76%
“…In the second ion source (IS 2 in Figure 1), the selected droplets were crossed with a 175-µA electron beam and an electron energy of 60 eV. The contribution of multiply charged precursor droplets was very low, although only 4 million He atoms were sufficient to stabilize two negatively charged ionic centers [34]. Plotting the curve versus the reciprocal of the relative m/z value led to peaks centered at the corresponding charge state of the product ions (Figure 10b).…”
Section: Anions To Cationsmentioning
confidence: 99%
See 2 more Smart Citations
“…HNDs are produced via supersonic expansion of precooled (9-10 K) and pressurized (20-30 bar) He (purity 99.9999%) through a 5 µm pinhole nozzle into ultrahigh vacuum. With these stagnation conditions an average helium droplet size of a few millions He atoms is expected [65,66]. On the left side the helium droplets source, where HNDs are produced via supersonic expansion of precooled He gas into ultrahigh vacuum.…”
Section: Experimental Methodsmentioning
confidence: 99%